Análise bioeconômica de um modelo de produção de leitecaprino no semiárido - Lima Júnior, Agenor Correia de (2018)
The objective was perform a out a bioeconomic analysis of goat milk production in a production system model in semiarid. Two studies were carried out. The first one dealt with the analysis of goat milk production, according to lactation and genotype. The second, followed with the measurement of the production costs of the activity, specifically, presenting viable alternatives in the dairy activity with projects that aim to increase income in the productive units of the region. The production system was implemented at the Experimental Station Pendência, belonging to the State Agricultural Research Company of Paraíba (EMEPA-PB) and data collection was carried out between 2013 and 2016. Were analyzed data of 98 lactations of goats of the genetic groups: Anglo Nubian and Alpine crossbred goats, distributed in seven lactation seasons. The data were submitted to descriptive statistical analysis to obtain the results for the dispersion and position measurements. The average monthly milk production observed during the period from 2013 to 2016 was 1,153.43 kg, with a variation from 359.84 to 2,729.49 kg. The total milk production (PTL) in the lactations presented an amplitude of 201.65 to 572.06 kg. The highest duration of lactation (DL) (258 days) occurred in the sixth lactation season. The lowest average milk production occurred in the third season (1.45 kg/animal/day) and the highest was observed in the sixth lactation season (1.91 kg/animal/day). The Alpine crossbred goats presented a mean of higher PTL in 23.22% in relation to Anglo Nubians. The use of techniques such as the establishment of three breeding seasons per year to achieve the goal of three calving seasons per year is, therefore, an important strategy for producers who provide milk for consumption "in nature", or for those engaged in the manufacture of dairy products, to maintain the availability of goat's milk regularly throughout the year. In the second, the structure of cost of production contemplated was that of Operational Cost. The total milk production in the analyzed period increased by 81.57%. There was an average productivity ranging from 0.97 to 1.44 L/animal/day. Gross income (RB) was not sufficient to cover the total costs in the three years analyzed in the dairy activity. The effective operating cost (COE) had an average percentage of 89.14% in the years studied. Dairy activity presented negative results for Gross Margin (MB), Net Margin (ML) and Profit. The alternative scenario of the cheesemaking activity presented ML of R$ 5,808.68 and Profit of R$ 3,798.68. It is necessary to mention that only the improvement in the productive efficiency of the production system, with the adoption of practices of food, genetic, reproductive and sanitary management, coupled with a constant policy of readjusting the price of the liter of milk paid to the producer, will enable the increase of income in the productive units. The specific proposal in this work verified that the alternative scenario of the cheesemaking activity presented viability with increased incomes in relation to the milk activity.